Principles of marketing - Medina, Roberto G. (Manila, Philippines : Rex Book Store, 2008)
Three new chapters are added to the original fourteen, "Consumer Behavior" , "The Buying Behavior of Organizational Markets" and "Mini-Cases".
CHAPTER 1. An Overview of Marketing -- 2. Consumer Behavior -- 3. The Buying Behavior of Organizational Markets -- 4. Market Segmentation and Targeting -- 5. Marketing Research and information systems -- 6. The Product -- 7. The Price -- 8. Marketing Channels -- 9. Physical distribution -- 10.T Retailing and wholesaling -- 11. Personal Selling -- 12. Advertising, Public relations and Sales Promotion -- 13. Services Marketing and Non- Business Marketing -- 14. International Marketing -- 15. Marketing Planning and control -- 16. Marketing and society -- 17. Mini-Cases.
Includes bibliographical references and index.
Keywords: MANAGEMENT